Self-splicing intron RNAs: ribozymes, parasites and agents of genomic change - Pyle, Anna Marie (Henry Stewart Talks, 2007)
Different classes of introns, Autocatalytic group I and group II introns, Discovery of self-splicing, Converting a self-splicing RNA into a multiple-turnover enzyme, The "tetrahymena ribozyme" and discovery of RNA catalysis, New insights into molecular recognition of RNA, Group I intron structure and catalytic mechanism, Group I intron applications, Group II introns and the big picture, Discovery of self-splicing by group II introns, Chemical mechanism of group II intron reactions, Catalytic engines for driving eukaryotic evolution, Explaining specificity of group II ribozymes, Group II intron ribozymes as model systems for RNA folding, Group II ribozymes as model systems for RNA tertiary structure, Nucleotide analog interference mapping, Current map of important atoms, Nucleotide analog interference suppression, Lambda-lambda interaction, 3D model of ai5gamma intron, Group II introns as tools and therapeutics
Reviewed at 2016/01/19